A study on traditional practice of head-shaving in newborn care among mothers in a tertiary care centre in Malda, West Bengal, India - Sahoo, Sushama; Singh, Arpita (International Journal Of Community Medicine And Public Health, 2020)
Background: Newborn period is culturally and traditionally sensitive in every society. Different communities have different traditional practices when it comes to taking care of newborn. Head-shaving in newborn period is one such unique traditional practice existent among rural population of West Bengal. This study was conducted to explore the traditional practice of head-shaving and to highlight its related morbidities among newborns following head-shaving. Methods: This was a descriptive, cross-sectional study conducted at triage of special newborn care unit of Malda Medical College and Hospital among 650 mothers who presented to us with their sick newborns following head-shaving. After obtaining informed consent, mothers were interviewed. The data were collected using pre-designed questionnaires. Statistical analyses of the data were done using SPSS version 21. Results: In the present study, majority (52.62%) of the mothers were within the age group of 18-21 years and 94.15% belonged to Muslim community. Neonatal head-shaving was usually done on 4th day of life (48.15%) and on 10th day of life (28.77%). Baby bath following head-shaving was given in 49.54% newborns using pond water and 77.70 % mothers used crude mustard oil for massaging following baby bath. Following head-shaving, 37.69% of newborns presented with poor feeding, 33.23% with abdominal distension and 61.23% presented with respiratory distress. Conclusions: Findings of present study highlights the harmful aspects of traditional practice of head-shaving among newborns in rural Bengal. This practice can be avoided by proper health education and counselling of the mothers and her associates involved in newborn care.